Chaotic behaviour of the Earth System in the Anthropocene - A.E. Bernardini; O. Bertolami; F. Francisco (Evolving Earth)
It is shown that the Earth System (ES) can, due to the impact of human activities, behave in a chaotic fashion. Our arguments are based on the assumption that the ES can be described by a Landau–Ginzburg model, which on its own allows for predicting that the ES evolves, through regular trajectories in the phase space, towards a Hothouse Earth scenario for a finite amount of human-driven impact. Furthermore, we find that the equilibrium point for temperature fluctuations can exhibit bifurcations and a chaotic pattern if the human impact follows a logistic map. Our final analysis includes interactions between different terms of the planetary boundaries (PB) in order to gauge the predictability of our model.